Student Voice in Personal Tutoring - Raby, Alison (Frontiers in Education, 2020)
This study focuses on student voices within personal tutoring at the University of Lincoln. It asks : What do students think of their personal tutoring experience ? Do students see themselves as partners with their tutors? What language do they use to describe this relationship? How does the experience of international students compare with home students? A literature review was conducted into student voice and engagement, personal tutoring, and international students. The study began with an online survey around students' experiences of personal tutoring. Subsequently, one-to-one semi-structured interviews were conducted with 30 students across the university. A good proportion of students stated that they would seek advice from their personal tutors first about a range of issues. However, a number of students maintained that they would approach the most relevant person directly. The majority of students experienced a positive relationship with their personal tutors. However, a small number found their tutor distant or unfamiliar. Group tutorials were largely found to be useful spaces for students to express their voices. Differences were identified in the experience of international students, most saying that they would contact friends and relatives before using their personal tutor. In conclusion, it is recommended that all staff receive training on referrals, and tutors responsible for international students should receive more training. The findings indicate that personal tutors could play an important role in enabling students’ voices to be heard and could be a vital source of help for international students transitioning into UK Higher Education.